Torque ripple reduction technique with improved flux response for a direct torque control induction motor drive - Singh, B.; Jain, S.; Dwivedi, Sanjeet Kumar (The Institution of Engineering and Technology, 2013)
The availability of limited voltage vectors in a conventional direct torque control drive fed from a two-level inverter causes torque and current ripples. In this study, a new torque ripple reduction technique with a modified look up table incorporating a larger number of synthesised non-zero active voltage vectors is proposed to overcome the limitations of the conventional and duty ratio control switching strategies. The voltage vector selection criteria in the proposed technique are based to prevent the stator flux demagnetisation during the low-speed operation with significant reduction in torque and current ripple. The proposed switching strategy is investigated through simulation and experimentally validated on a test drive.